Fundamentals of the probative activity in the Spanish Civil process - Sigüenza López, Julio (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
To win a lawsuit, being right is so important as knowing how to prove the right to those requested. This shows the practical relevance of the evidentiary activity and the need to know properly its most featured aspects. To that end, the current study analyze the principles that must be taken into account in this matter, what should be proved, who has the burden of proving the facts that are asserted in a court of law, and what needs to be used to try justify the allegations made in court.